Epiglottic dermoid cyst: a rare case report - ., Ramchandra; Nandyal, C. B.; Deshmukh, Kiran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Epiglottis dermoid cysts are generally benign lesions, which can affect all the age groups. Dermoid cysts arising from the head and neck region are rare, slow growing, and well-circumscribed neoplasm. Symptoms are non-specific and usually related to the size and the location of the lesion. A dermoid cyst of the epiglottis is extremely rare. To the best of our knowledge, only one case has been previously reported in the English literature and a total of three cases were presented in Russian literature in two studies. In our report, a middle-aged male presented with foreign body sensation in throat for 1-year and difficulty in swallowing for three months, mainly for solids. Thorough history, clinical examination and relevant investigation were done. Direct laryngoscopy was done and complete surgical excision was done. The aim of the case report is to present a rare case of epiglottic dermoid cyst, its clinical presentation, radio-logical features and surgical management.